Photodegradation of Chlordane in Soil and Water Matrix Using Induced UV and Solar Light - Alexander C Sioson; Susan M Gallardo (ASEAN Journal of Chemical Engineering, 2007)
The photodegradation of chlordane in soil and water matrix using induced ultraviolet (UV) radiation and solar light was evaluated in this study. A batch photolytic reactor equipped with a low-pressure mercury lamp (17 W) sterilight ultraviolet (UV) lamp with a supplied wavelength of 254nm was used in the photodegradation experiments. The pesticide’s initial concentration in water was varied using three different concentrations (0.80, 2.60, and 8.0 mg/L) and soil samples were prepared at three different dosages (0.20, 2.0, and 4.0 mg/kg). At preferred time intervals, samples were withdrawn from the reactor. The pH and temperature of the samples were continuously monitored. Samples were extracted using solid-phase extraction (SPE) and the degradation of components was verified using a GC-ECD setup. Solar experiments were conducted during the months of April and May (140 33.971’N, 1200 59.515’E); with a mean sunlight intensity of 85,187.5 lux. Results of the photodegradation experiments using the batch photolytic reactor showed an average of 91.65% degradation of the chlordane pesticide dissolved in water after hours of exposure to UV light. High degradation efficiencies were achieved at higher chlordane initial concentrations. For solar photodegradation experiments, an average of 71.59% degradation was achieved. Photodegradation in soil showed an average of 62.54% degradation of the compound. As such, percentage degradation increases as the initial concentration of the pollutant increases. Further, solar photodegradation experiments in soil samples showed an approximate 56.35% degradation of the compound throughout the duration of the experiment. Chloride-ion analysis using high-performance liquid chromatography (HPLC) equipment was conducted at chlordane aqueous solution. At higher chlordane concentrations, higher chloride ion concentrations in the solution were achieved. As such, more chloride ions detached themselves from the parent compound every two hours of sampling time and soon reached an almost steady state concentration at a maximum exposure time of eight hours.